Introduction - Camille Bloomfield; Audrey Ziane (Itinéraires)
This introduction attempts to define the notion of manifesto by recalling its fundamentally interdisciplinary character, as well as its varying success in the eyes of both critics and artists. Inspired by the works of Perriault and Besnier, the notion of interdisciplinarity is linked to that of “indiscipline” in order to highlight the need for a transversal and fluid approach to knowledge. The paper also analyses the methodology of some contributions to the issue that make use of a database (the Manart database), a tool that’s main function is to classify, to work on hybrid documents such as manifestos. Their scientific protocol must be made explicit and refer to a broader reflection on digital humanities. Finally, the paper addresses the politics of manifestos, while studying the various discourses and acts of indiscipline contained in the issue, and turns our interest to the ones that benefit of the manifesto, this form of confrontation which is often hijacked for contradictory purposes.